A crença religiosa sob a perspectiva semiótica de Peirce - Bortolotti, Ricardo Gião [UNESP] (Universidade Estadual de Maringa, 2014)
Current paper presents the relationships between beliefs, specifically religious ones, and the Peirce’s theory of interpretants. It is assumed that religious belief emphasizes the emotional aspect of faithful, preventing criticism and change of habit. According to the author, the nature of cognition is contrary to the determination of this kind of belief since it is based on the method and fallibility of hypotheses. It is not enough for the method to deduce its consequences but seeks the inductive verification of their results in the long run and through the community of beings who thinks through signs. The problem of religious belief is the acceptance of a transcendent world and intuition which guides behavior. The vague idea of God is not submitted to scientific hypotheses but, engendered by religious systems, it creates signs whose emotional appeal is evident, redirecting it to its own target principles. Therefore, is repeats the success achieved in the past by dogmas, which were effective to appease the anguish of the believer and reproduce order. Knowledge should not have any boundaries because it is grounded on the method and cognition of reality.

Esse artigo pretende apresentar algumas relações entre as crenças, especificamente a religiosa, e a teoria dos interpretantes de Peirce. Parte-se, pois, do pressuposto de que a crença religiosa enfatiza o aspecto emocional do fiel, impedindo a crítica e a mudança de hábito. Segundo o autor, a natureza da cognição é contrária à determinação desse tipo de crença, uma vez que se fundamenta no método e no falibilismo de nossas hipóteses. Tal método não se contenta em deduzir suas consequências, mas busca, ao longo do tempo, e por intermédio da comunidade de seres que pensam por meio de signos, a verificação indutiva de seus resultados. O problema da crença religiosa está na aceitação de um mundo transcendente e na intuição que servem de orientação para a conduta. A ideia de Deus, sendo vaga, não se submete aos critérios de verdade das hipóteses científicas, mas engendrada pelos sistemas religiosos cria signos cujo apelo emocional é evidente, reorientando-os para finalidades próprias. Repete, portanto, o sucesso que o dogma alcançou em fórmulas passadas e que foram eficazes para aplacar a angústia do crente e reproduzir a ordem. O conhecimento não deve ter fronteiras, pois alicerçado no método e na cognição do real.
Religious belief in Peirce´s semiotic perspective
Keywords: Science; Emotion; Interpretants; Sacred; Signs; Feelings; Ciência; Emoção; Interpretantes; Sagrado; Sentimentos; Signo